A small molecule SMAC mimic LBW242 potentiates TRAIL- and anticancer drug-mediated cell death of ovarian cancer cells. - Eleonora Petrucci; Luca Pasquini; Manuela Bernabei; Ernestina Saulle; Mauro Biffoni; Fabio Accarpio; Simone Sibio; Angelo Di Giorgio; Violante Di Donato; Assunta Casorelli; Pierluigi Benedetti-Panici; Ugo Testa (PLoS ONE, 2012)
BACKGROUND: Ovarian cancer remains a leading cause of death in women and development of new therapies is essential. Second mitochondria derived activator of caspase (SMAC) has been described to sensitize for apoptosis. We have explored the pro-apoptotic activity of LBW242, a mimic of SMAC/DIABLO, on ovarian cancer cell lines (A2780 cells and its chemoresistant derivative A2780/ADR, SKOV3 and HEY cells) and in primary ovarian cancer cells. The effects of LBW242 on ovarian cancer cell lines and primary ovarian cancer cells was determined by cell proliferation, apoptosis and biochemical assays. PRINCIPAL FINDINGS: LBW242 added alone elicited only a moderate pro-apoptotic effect; however, it strongly synergizes with tumor necrosis factor-related apoptosis inducing ligand (TRAIL) or anticancer drugs in inducing apoptosis of both ovarian cancer cell lines and primary ovarian cancer cells. Mechanistic studies show that LBW242-induced apoptosis in ovarian cancer cells is associated with activation of caspase-8. In line with this mechanism, c-FLIP overexpression inhibits LBW242-mediated apoptosis. CONCLUSION: LBW242 sensitizes ovarian cancer cells to the antitumor effects of TRAIL and anticancer drugs commonly used in clinic. These observations suggest that the SMAC/DIABLO mimic LBW242 could be of value for the development of experimental strategies for treatment of ovarian cancer.